An Investigation on the Variety of English Used by Students in the ESL Classroom - V. Damodaram, Josephine Leela (1998)
This study reports and discusses some of the common features evident in an English written composition of a group of Form Five students' from the districts of Kuala Pilah and Seremban in Negeri Sembilan. The results of the analysis suggest that the salient features identified in the written compositions are features of Malaysian English, which has been recognised as a new nonnative variety of English.